PENENTUAN KESETIMBANGAN, TERMODINAMIKA DAN KINETIKA ADSORPSI ARANG AKTIF TEMPURUNG KELAPA SAWIT PADA ZAT WARNA REACTIVE RED DAN DIRECT BLUE - Rensy Aula Sari; M. Lutfi Firdaus; Rina Elvia (ALOTROP, 2017)
This perpose of this research was to know the isotherm, kinetics and thermodynamics adsorption of synthetic  dye onto activated carcoal from palm oil shell. The synthetic dye were Reactive Red and Direct Blue. The model of isotherm were Langmuir and Freundlich, kinetics adsorption tested were Pseudo orde-1 and Pseudo orde-2, and also thermodynamics were free energy change (?Go), enthalpy change (?Ho), and entropy change (?So). The dominant isotherm adsorption was isotherm Freundlich, kinetic adsorption Pseudo 2 th order  with the value (?So), (?Go) and (?Ho), Reactive Red were 0,0028 Kj/mol.K , -3,93 Kj/mol, and -36,12 Kj/mol respectively. Whereas in direct blue were 0,0034 Kj/mol.K, -1,67 Kj/mol,and -30,16 Kj/mol respectively.